The Effect of Institutional Ownership, Independent Board of Commissioners and Audit Committee Good Corporate Governance on Earnings Management - Masruri, M Anwar; Irsyad, Fatih Mohammad; Asvariwangi, Verni (Universitas Ibn Khaldun Bogor, 2023)
In this study, corporate governance is measured using institutional ownership, independent board of commissioners and audit committee to see its effect on earnings management as measured using discretionary accruals based on Jones cross sectional, the data used are food and beverage subsector manufacturing companies from 2018 - 2022 with a total sample that matches the predetermined criteria of 55 sample companies, based on the results obtained, it states that institutional ownership has a negative effect on earnings management, while other variables have no effect this can be caused by the number of samples and control variables that have not been added in this study